Design Epistemology - Dino Karabeg (Information, 2012)
The liberation from the view that only one way of making sense of experience is legitimate (the one that “corresponds to reality”), which follows from the results of 20th century science and philosophy, puts us into a position to consciously choose and assign a purpose to the creation of meaning; and based on that choice, to develop completely new modes of information, to suit each chosen purpose. We present an instance of this approach, where information and knowledge work are considered as key societal systemic components, and then designed as it may best suit the various functions that pertain to this role, notably the function of illuminating the way to all other systemic self-organization. Design epistemology provides an academic foundation for this approach; the Knowledge Federation community implements it in practice.